The Affordable City : Strategies for putting housing within reach (and Keeping It There) - Phillips, Shane (Washington, DC : Island Press, 2020)
From Los Angeles to Boston and Chicago to Miami, US cities are struggling to address the twin crises of high housing costs and household instability. Debates over the appropriate course of action have been defined by two poles: building more housing or enacting stronger tenant protections. These options are often treated as mutually exclusive, with support for one implying opposition to the other. Shane Phillips believes that effectively tackling the housing crisis requires that cities support both tenant protections and housing abundance. He offers readers more than 50 policy recommendations, beginning with a set of principles and general recommendations that should apply to all housing policy. The remaining recommendations are organized by what he calls the Three S's of Supply, Stability, and Subsidy. Phillips makes a moral and economic case for why each is essential and recommendations for making them work together. There is no single solution to the housing crisis$1 (Bit will require a comprehensive approach backed by strong, diverse coalitions. The Affordable City is an essential tool for professionals and advocates working to improve affordability and increase community resilience through local action.s
Part I: Principles and General Recommendations -- Part II: Policies -- Part III: Bringing It All Together.
3 user
Keywords: HOUSING POLICY -- UNITED STATES; HOUSING -- UNITED STATES